Amauroderma rugosum (Blume & T. Nees) torrend attenuates the pathophysiological cascade of inflammatory events in epileptogenesis / Chan Pui Mun - Chan, Pui Mun (2016)
Amauroderma rugosum has been used as a remedy to prevent epileptic episodes, incessant crying by babies and cancer, reduce inflammation, and treat diuresis and upset stomach by the indigenous people in Malaysia and the Chinese in China. To date, the medicinal properties and traditional beliefs of A. rugosum are yet to be explored and verified. Hence, the aims of this study are to show the successful cultivation of A. rugosum and evaluate the antioxidant, anti-inflammatory, anti-neuroinflammatory, and anti-epileptic activities using in vitro and in vivo approaches. Based on the results obtained, mycelium of A. rugosum has good source of nutrients. Besides that, hexane fraction (HF) from mycelium, ethanolic extracts of wild (WB) and domesticated (DB) basidiocarps of A. rugosum showed significant antioxidant, anti-inflammatory, and anti-neuroinflammatory activities. HF was selected for in-depth study on the modulation of neuroinflammatory pathways and anti-epileptic activity. HF was the most effective nitric oxide (NO) scavenger and NO production inhibitor in lipopolysaccharide (LPS)-stimulated macrophage (RAW264.7) and microglia (BV-2) cells. The inhibition of NO productions was mediated through the down-regulation of inducible nitric oxide synthase (iNOS) expression. Besides, HF significantly suppressed the inflammatory cytokine such as tumour necrosis factor alpha (TNF-α) and up-regulated anti-inflammatory cytokine, interleukin-10 (IL-10) in macrophage cells. Furthermore, HF was found to down-regulate proinflammatory cytokines (IL-1α, IL-1β, and IL-6) and other proinflammatory (Traf1, Traf2, and Cd14) gene expressions in microglial cells. In addition, HF up-regulated anti-inflammatory genes such as Nfkbia and Nfkbie. In vivo assessment in rats revealed that HF could ameliorate epileptic seizure behaviours such as wet dog shakes, facial myoclonia, and paw tremor. Two major compounds were detected in HF which includes ethyl linoleate and ergosterol. In conclusion, HF iii exhibited antioxidant activity and attenuated proinflammatory mediators and epileptic seizure behaviours. Therefore, A. rugosum may serve as a potential therapeutic agent in the management of inflammation leading to epilepsy.